Assessment of nurses’ knowledge on rotahaler device in a teaching hospital of central Nepal - Piryani, R M; Poudel, R S; Shrestha, S; Prajapati, A (Journal of Chitwan Medical College, 2017)
Nurses are among the key personnel for educating patients on use of inhalers. This study aimed to assess the baseline knowledge of practitioner nurses on rotahaler technique and management. A descriptive study was conducted among the practitioner nurses (n=31) in a teaching hospital of Central Nepal. Knowledge on rotahaler technique and management were assessed using questionnaire by giving ‘1’ for correct response and ‘0’ for incorrect response. Descriptive statistics was calculated for statistical analysis using IBM-SPSS 20.0. The mean knowledge score of the participants was 4.74±1.56. Majority of the participants (76.7%) were unable to respond that dry powder inhalers (DPIs) allow maximum deposition of drugs in lung than pressurised metered dose inhalers (pMDIs) and only 2 (6.5%) of them was aware of instructions to clean the rotahaler. About 50% of participants were unaware that patient with asthma and chronic obstructive pulmonary disease (COPD) should hold their breath for around 10 seconds after taking inhaled medication. Similarly, two third participants knew that a quick, forceful and deep inspiration is necessary while using rotahaler. The participating nurses had inadequate knowledge on the technique of rotahaler and its management. Nurses in hospital setting need continued education and training on inhalation technique and the management of inhalation devices.